The Analysis of Building Façade Sheltering by Integrated Energy Simulation. (November 2015) - You, Wei; Ding, Wowo
Abstract: This paper investigates the influence of the uneven façade design on energy consumption from a integrated perspective. The computer simulation techniques were adopted to assess the effects of the façade sheltering sizes on the total energy consumption. To facilitate the model establishment, some scripts are written by MATLAB. The simulation results indicate that the façade sheltering generally makes the energy consumption increase, regardless of the sheltering types. And the influence range of the sheltering on the total energy consumption relates closely to the sheltering condition and the façade window position.